Mitigation of Terrain Effects using Beamforming Antennas in Ad Hoc Networks - Ramakrishnaiah, Vinay B; Kubichek, Robert F; Muknahallipatna, Suresh (Discoveries in Agriculture and Food Sciences, 2019)
Wireless communication is sensitive to ambient noise as well as interference due to the use of a shared medium. The link quality is significantly affected by the surrounding terrain including buildings, hills, foliage, etc. Terrain changes also pose a problem for communication and localization in mobile ad-hoc networks and in the deployment of Internet of Things (IoT). Many of these problems can be addressed through careful antenna design, but these can be challenging as they require complex hardware and software. We propose a new approach called virtual terrain leveling (VTL), which acts as a trade-off between the complex antenna design approaches and the simple omni-directional antennas. VTL virtually nullifies the effects of the terrain using phased array antennas to compensate for the path losses. Convex optimization and the Nelder-Mead simplex method are used to compute the antenna array weights that minimize the error between the ideal and achieved beam patterns. Simulations are performed in the presence of different terrains and the received power at varying distances from the transmitter is analyzed. The results show improved received power up to a specified distance from the transmitter and then power decays rapidly with increasing distance, indicating interference reduction.